Antioxidative response of Indian mustard subjected to drought stress - Nisha Kumari; Ram Avtar; Anita Kumari; Bunty Sharma; Babita Rani; RK Sheoran (Journal of Oilseed Brassica, 2026)
The growth and yield of plants are severely affected by different environmental stresses. Water deficit imposed bydrought brings about severe growth retardation and yield loss of crops. Therefore, in order to evaluate the response ofantioxidant defense system of Indian mustard varieties to drought stress, a field experiment was conducted at OilseedsResearch Area, CCS HAU, Hisar, by taking two varieties i.e. RH 0406 (drought-tolerant) and RH 0749 (drought-sensitive).A different response of drought stress was observed on enzymatic and non-enzymatic components of antioxidantsystem in leaves of drought-tolerant and drought-sensitive varieties of Indian mustard (Brassica juncea). Droughtstress was created by withholding the irrigation after sowing. The antioxidative enzymes viz. superoxide dismutase(SOD), peroxidase (POX), ascorbate peroxidase (APX) and glutathione reductase (GR) showed higher basal activities inleaves of drought-tolerant variety (RH 0406) as compared to drought-sensitive variety (RH 0749). Plants under droughtstress indicated a significant increase in antioxidative enzyme but this increase was more pronounced in droughttolerantvariety i.e. RH 0406 as compared to RH 0749, a drought sensitive variety. The content of ascorbic acid, carotenoids,total glutathione and proline content were also recorded higher in tolerant variety than in sensitive variety underdrought stress. It can be inferred that leaves of drought-tolerant variety (RH 0406) had greater capacity to performreaction of antioxidative pathways under drought stress to control drought-induced oxidative stress.